MANAJEMEN STRATEGIS KEPALA MADRASAH DALAM PENGUATAN PROGRAM RISET - Nurul Fatimah; Adri Efferi; Mufatihatutut Taubah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the strategies employed by the madrasah principal in developing the research program at MAN 1 Kudus, focusing on three aspects: the implementation of the research program, the leadership strategies of the principal in enhancing the program, and the evaluation of its implementation. This research is a field study using a qualitative approach. The research subjects were selected through purposive sampling to obtain relevant informants. Data were collected through interviews, observations, and documentation, and validated using source triangulation. The data were analyzed inductively to explore findings in depth. The study shows that the implementation of the research program at MAN 1 Kudus is carried out through the application of management functions, the organization of supervising teachers, and the execution of various research activities. The principal’s strategies in developing the research program include strengthening regulations, improving the capacity of research supervisors, collaborating with universities and research institutions, providing adequate facilities and infrastructure, and publishing achievements to enhance student motivation and the madrasah's image. Evaluation is conducted through regular coordination meetings, which are then used as the basis for program improvement and enhancing the quality of students' research outputs. This research offers a new contribution in the form of a strategic model for developing research programs based on madrasah leadership, integrating management functions, institutional collaboration, and a culture of publication.